The invisible truth: Secrets behind steganography - Quinto, Amando Jose (Animo Repository, 2008)
This study presents a detailed discussion on what steganography is and its relations to coding theory from the paper fast communication steganography and error-correcting codes by Munuera [9]. To understand this, several theorems and concepts on stenography are introduced and is compared to the concepts in coding theory. A java program was also created to illustrate how the Least Significant Bit algorithm works. Basic terminologies and concepts on codes and algebra were included to let the readers understand the protocols and theorems that are discussed.